Integration of ZnO nanorods with MOS capacitor for self-powered force sensors and nanogenerators. (17th August 2021) - Geng, Yulin; Bin Che Mahzan, Muhammad Ammar; Jeronimo, Karina; Saleem, Muhammad Mubasher; Lomax, Peter; Mastropaolo, Enrico; Cheung, Rebecca
Abstract: In this work, we present a novel force-sensing device with zinc oxide nanorods (ZnO NRs) integrated with a metal-oxide-semiconductor (MOS) capacitor and encapsulated with Kapton tape. The details of the fabrication process and working principle of the integrated ZnO NRs-MOS capacitor as a force sensor and nanogenerator have been discussed. The fabricated ZnO-MOS device is tested for both the open-circuit and resistor-connected mode. For an input force in the range of 1–32 N, the open-circuit output voltage of the device is measured to be in the range of 60–100 mV for different device configurations. In the resistor-connected mode, the maximum output power of 0.6 pW is obtained with a 1 MΩ external resistor and input force of 8 N. In addition, the influence of different seed layers (Ag and ZnO) and the patterning geometry of the ZnO nanorods on the output voltage of ZnO-MOS device have been investigated by experiments. An equivalent circuit model of the device has been developed to study the influence of the geometry of ZnO NRs and Kapton tape on the ZnO-MOS device voltage output. This study could be an example of integrating piezoelectric nanomaterials on traditional electronic devices and could inspire novel designs and fabrication methods for nanoscale self-powered force sensors and nanogenerators.